THE HISTORY OF THE JALAL-ABAD TEACHERS’ INSTITUTE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The main topic of the scientific article is the history of Jalal-Abad Teachers’ Institute for 1948-1955, which analyzes the issues of education, public enlightenment in the historical aspect. The main purpose is to explain the history of Jalal-Abad Teachers’ Institute, to supplement the domestic historical educational, enlightenment orientation. When preparing the scientific article, the methods used in science were taken into account, the principles of systematicity, objectivity, development, universal connection and historicity were fully observed, which allowed to find new data as a result of the method of sorting and historical comparison of data. The method of hermeneutics helped to clarify with historical facts the information about the teachers’ institute organized in the city of Jalal-Abad in 1948-1955, and the methods of analysis and synthesis, induction and deduction, transition from abstract to concrete, logical conclusion helped the research activity to achieve the result. As the main results of the research activity were collected data stored in the funds of the Central, regional archives, historical works, the history of Jalal-Abad Teachers’ Institute was written. The scientific value of the researched topic is that it contributes to the clarification of the history of education, the dynamics of spiritual culture of Kyrgyzstan. The recommendation to use the results of the study of this topic as a material for teaching the history of Kyrgyzstan emphasizes its practical importance. This work contributes to the elucidation of the history of educational institutions in the south of Kyrgyzstan and the continuation of scientific work on the topic.
Keywords: illiteracy, pedagogical personnel, enlightenment, pedagogical activity, intellectuals, scientist, education, public enlightenment.